Scroll, Click, Buy: The Influence of Digital Marketing, Engagement, and Brand Awareness on Gen Z Indonesia's Purchase Intentions - Suleman, Dede; Zuniarti, Ida; Puspasari, Aprilia; Joesah, Nurzalinar; Hakim, Lukman (Future Science / FSH-PH Publications, 2025)
This study examines the influence of digital marketing experience, engagement, and brand awareness on the purchase intentions of Generation Z in Indonesia. Drawing from the Stimulus–Organism–Response (SOR) and Cognitive–Affective–Conative (CAC) models, this research integrates emotional and behavioral responses to short-form digital marketing content. A quantitative design using Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed on 220 active Gen Z social media users. The results reveal that digital marketing experience significantly affects engagement and brand awareness, which in turn drive purchase intention. The findings underscore the importance of emotional engagement and authenticity in enhancing consumer response to short video marketing. The study extends the CAC model into the short video marketing context and offers practical implications for digital marketers.re effective and impactful digital marketing strategies.